2022
DOI: 10.1080/1369118x.2022.2161827
|View full text |Cite
|
Sign up to set email alerts
|

Politicizing for the idol: China’s idol fandom nationalism in pandemic

Abstract: We like to thank Aofei Lv for inspiring this research, Anfan Chen for sharing the Weibo-Cov dataset, and Bingchun Meng for providing valuable comments on the draft paper. We thank Zhe Chen, Jiawen Cui, Zhenyu Zhang, Juemin Zhang, and Yufan Li for their superb research assistance. Finally, we would also like thank the anonymous reviewers and the editors of this special issue, Stephen D. Reese, Wenhong Chen, Zhongdang Pan for their constructive feedback and comments on this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Even during the amendment protests of "Draft Hong Kong Extradition Ordinance" in 2019 and during the Covid-19 epidemic, female fan groups in China used their organised management experience and familiarity with social media platforms to successfully mobilise two large-scale cyber-nationalist actions. Constructing the country as an idol, they used digital Internet technology to form a powerful unorganised organisational force by accessing blocked foreign social networking sites and attacking posts critical of the Chinese government therein, making a significant contribution to defending the image and interests of the country as an idol [41,42].…”
Section: Female Fansmentioning
confidence: 99%
“…Even during the amendment protests of "Draft Hong Kong Extradition Ordinance" in 2019 and during the Covid-19 epidemic, female fan groups in China used their organised management experience and familiarity with social media platforms to successfully mobilise two large-scale cyber-nationalist actions. Constructing the country as an idol, they used digital Internet technology to form a powerful unorganised organisational force by accessing blocked foreign social networking sites and attacking posts critical of the Chinese government therein, making a significant contribution to defending the image and interests of the country as an idol [41,42].…”
Section: Female Fansmentioning
confidence: 99%
“…For instance, Wang (2020) conducted a case study about Luo Tianyi, a Chinese virtual idol, to analyze the power of virtual idols in communication strategy. The survey study mentioned that the popularity of Luo Tianyi suggested a shift in discourse power from enterprises to audiences and indicated that Luo Tianyi enjoyed a high level of consumer recognition and satisfaction when she was used in product endorsements (Wang, 2020). However, are virtual idols as effective as traditional celebrities and online influencers in product endorsements?…”
Section: Types Of Celebrity Endorsers In Advertising Their Characteri...mentioning
confidence: 99%
“…This shift has allowed fandoms to push far beyond organized appreciation of an artist or art and into highly efficacious political activity (Dean, 2017;Petersen et al, 2023). Studies in this vein have described how fandoms influence online and real-life events, such as helping enforce censorship and disseminating talking points of the state (Luo & Li, 2022;Wang & Luo, 2023).…”
Section: Fandomsmentioning
confidence: 99%
“…K-Pop fandoms have emerged as a unique and influential force in the global entertainment industry, with a massive and engaged fanbase that extends beyond entertainment consumption (Wang & Luo, 2023).…”
Section: K-pop and Btsmentioning
confidence: 99%